Wear behaviour of novel Al based composite reinforced with ceramic composite (Al2O3–SiC–C) developed from colliery shale material. (September 2014) - Siva S. B, V.; Ganguly, R. I.; Srinivasa Rao, G.; Sahoo, K. L.
<x content-type="archive" xml:space="preserve">Abstract</x> The paper deals with the wear behaviour of the newly developed composite reinforced with a novel ceramic composite. The wear study is made through pin-on-disc wear test under three loads, namely 20, 40 and 60 N for a sliding distance of 2·52 km. Al colliery shale (CS) composite has shown excellent wear resistance compared to the other two composites (taken as a reference for comparison) i.e. Al–Al2O3 and Al–Al2O3–SiC. The presence of carbon in the form of graphite in Al–CS composite has enhanced the resistance to wear and reduced coefficient of friction. Wear rate is higher for the three composites initially up to 2·16 km of sliding distance and has then declined at higher sliding distance. It is observed that up to a sliding distance of 2·16 km the primary mode of wear is due to delamination and decohesion of the particles. As the sliding distance increases to 2·52 km the work hardening phenomenon plays a major role and the resistance to wear has increased for all the three composites. SEM photographs from the worn out surfaces have corroborated the results.